Indirect mineral carbonation of natural asphalt extraction solid waste residue via pH and temperature control - Michael Ambarita; Devit Ardiansyah; Wolfgang W. Schmahl; Yustina M. Pusparizkita; Rifky Ismail; J. Jamari; Athanasius P. Bayuseno (Case Studies in Chemical and Environmental Engineering, 2024)
This study investigated the recycling of solid waste residues from rock asphalt extraction via 5-h calcination at 900 °C and indirect carbon mineralization. The calcined powder was first dissolved at 60 °C in 2 M CH3COOH, carbonized in NH4HCO3, and agitated at 1200 rpm in 2 M NaOH for 30 minutes at 30–60 °C and pH 12. The precipitated calcium carbonate (PCC) results are calcite (24.4–56.3 wt%) and vaterite (75.6–3.7 wt%), as confirmed by XRD analysis, carbonate FTIR spectra, and SEM images of prismatic calcite and spherical vaterite. This high-value PCC product has potential industrial applications, such as paper and plastics.